Public sector pensions. - Rhodes, Gerald (Published for the Royal Institute of Public Administration [by the] University of Toronto Press, 1965)
This is the first book to offer a fundamental analysis of public sector schemes. It takes a new look at a whole trange of problems affecting the retirement benefits of most of the population and ends with some very challenging, positive proposals.